Uniaxial ratcheting deformation of 316LN stainless steel with dynamic strain aging: Experiments and simulation. (15th December 2020) - Sun, Xingyue; Xing, Ruisi; Yu, Weiwei; Chen, Xu
Highlights: Cyclic experiments of 316LN SS are conducted at different temperatures. The effect of dynamic strain aging on cyclic deformation is analyzed. A unified constitutive model is proposed to describe DSA at different temperatures. A hardening parameter is introduced to improve the forecasting accuracy of DSA. Abstract: Dynamic strain aging (DSA) widely exists in austenitic stainless steel at elevated temperature. The materials will be drastically strengthened by this phenomenon. A series of symmetric strain-controlled and asymmetric stress-controlled cyclic experiments were conducted at different temperatures from 293 K to 823 K for 316LN stainless steel. The DSA phenomenon was observed in all the tests under elevated temperatures and it became more significant with the increase of temperature until reached the maximum at 823 K. There were a series of manifestations of DSA such as the anomalous cyclic hardening with temperature increasing in the strain-controlled tests and the quick-shakedown of ratcheting strain in the stress-controlled tests. An appropriate constitutive model to describe the cyclic behavior at different temperatures is necessary. The proposed kinematic hardening model is based on Ohno-Wang model and modified by introducing a hardening index into dynamic recovery term. The index accounts for DSA hardening degree of material under high temperature, therefore the performance mentioned above can be simulated well by this proposed model. By relating the parameters with temperature and plastic strain amplitude, a unified visco-plastic constitutive model was proposed. Simulation results of the proposed model agree much better with experimental values.